Making Solar Cells a Reality in Every Home: Opportunities and Challenges for Photovoltaic Device Design - Rajendra Singh; Githin Francis Alapatt; Akhlesh Lakhtakia (IEEE Journal of the Electron Devices Society, 2013)
Globally, the cumulative installed photovoltaic (PV) capacity has topped the 100-gigawatt (GW) milestone and is expected to reach 200 GW by the year 2015. More than 90% of the installed PV capacity employs bulk-silicon solar cells. Engineering problems that include thermal and optical challenges have not permitted the large-scale commercialization of concentration PV systems, lack of functional reliability-and the concomitant lack of economic bankability-being a major barrier. For increasing the efficiency of single-junction cells beyond the Shockley-Queisser limit, several approaches based on concepts such as multiple exciton generation, carrier multiplication, hot-carrier extraction, etc., have been proposed; however, these do not seem to be commercially viable. Since both bulk-silicon and thin-film (amorphous silicon, cadmium telluride, and copper indium gallium selenide) solar cells remain as the only two commercially viable options for terrestrial PV applications, a multi-terminal multi-junction architecture appears promising for inexpensive PV electricity generation with efficiency exceeding the currently feasible 25%. The architecture exploits the present commercial silicon solar cells along with abundant and ultra-low-cost materials such as Cu2O. With the availability of well-controlled manufacturing processes at the sub 2-nm length scale, it will become possible to manufacture ultra-high efficiency and ultra-low cost PV electricity generation modules based on silicon.